The Effect of Pectin Concentration and Storage Time on the Quality of Pineapple Jam Sheet - Ahmad Ikhwal P; Zulkifli Lubis; Sentosa Ginting (Jurnal Rekayasa Pangan dan Pertanian, 2014)
Research was conducted to determine Effect of pectin concentration and storage time on the quality of pineapple jam sheet. Pineapple production in Indonesia is very abundant, but its processing is still very minimal, therefore the diversification of pineapple processing is needed to increase. This study was conducted to determine the effect of pectin concentration and storage time on the quality of pineapple jam sheet. This study used a completely randomized design with two factors namely pectin concentration (P): 0.25%, 0.50%, 0.75% and 1.00%, and storage time (L): 0 days, 5 days, 10 days and 15 days. The parameters analyzed were moisture content, total acid, vitamin C, total dissolved solids, total microbes, organoleptic of color, aroma, taste, texture as well as color and texture scores. The results showed that the concentration of pectin had highly significant effect on water content, total acid, vitamin C, total dissolved solids, organoleptic of color, aroma, taste, texture as well as color and texture scores. Storage time had highly significant effect on water content, total acid, vitamin C, total dissolved solids, total microbes, organoleptic of color, aroma, taste, texture as well as color and texture scores. Interaction of the two factors had highly significant effect on water content, total acid test scores and color. Concentration of 0.75% pectin gave the best quality characteristics of the pineapple jam sheet and storage for 10 days was still acceptable for consumption. Keywords: Pectin concentration, pineapple, pineapple jam sheet, storage time.